Antihypertensive Drugs, Prevention of Cognitive Decline and Dementia: A Systematic Review of Observational Studies, Randomized Controlled Trials and Meta-Analyses, with Discussion of Potential Mechanisms - Rouch, Laure; Cestac, Philippe; Hanon, Olivier; Cool, Charlène; Helmer, Catherine; Bouhanick, Béatrice; Chamontin, Bernard; Dartigues, Jean-Franҫois; Vellas, Bruno; Andrieu, Sandrine (CNS drugs, 2015)
Background Chronic hypertension, particularly midlife high blood pressure, has been associated with an increased risk for cognitive decline and dementia. In this context, antihypertensive drugs might have a preventive effect, but the association remains poorly understood. Objectives The aim of this systematic review was to examine all published findings that investigated this relationship and discuss the mechanisms underlying the potential benefits of antihypertensive medication use. Methods A literature search was conducted using MEDLINE, Embase, and the Cochrane Library for publications from 1990 onwards mentioning hypertension, antihypertensive drugs, cognitive decline, and dementia. Results A total of 38 relevant publications, corresponding to 18 longitudinal studies, 11 randomized controlled trials, and nine meta-analyses were identified from the 10,251 articles retrieved in the literature search. In total, 1,346,176 subjects were included in these studies; the average age was 74 years. In the seven longitudinal studies assessing the effect of antihypertensive medication on cognitive impairment or cognitive decline, antihypertensive drugs appeared to be beneficial. Of the 11 longitudinal studies that assessed the effect of antihypertensive medication on incidence of dementia, only three did not find a significant protective effect. Antihypertensive medication could decrease the risk of not only vascular dementia but also Alzheimer’s disease. Four randomized controlled trials showed a potentially preventive effect of antihypertensive drugs on the incidence of dementia or cognitive decline: SYST-EUR (Systolic Hypertension in Europe Study) I and II, with a 55 % reduction in dementia risk (3.3 vs. 7.4 cases per 1,000 patient years; p < 0.001); HOPE (Heart Outcomes Prevention Evaluation), with a 41 % reduction in cognitive decline associated with stroke (95 % confidence interval [CI] 6–63); and PROGRESS (Perindopril Protection against Recurrent Stroke Study), with a 19 % reduction in cognitive decline (95 % CI 4–32; p = 0.01). Meta-analyses have sometimes produced conflicting results, but this may be due to methodological considerations. The lack of homogeneity across study designs, patient populations, exposition, outcomes, and duration of follow-up are the most important methodological limitations that might explain the discrepancies between some of these studies. Conclusion Antihypertensive drugs, particularly calcium channel blockers and renin–angiotensin system blockers, may be beneficial in preventing cognitive decline and dementia. However, further randomized controlled trials with longer periods of follow-up and cognition as the primary outcome are needed to confirm these findings.